(untitled) (Almanack, 2024)
Resenha: Machado, A. R. de A.; Guerra Filho, A. (orgs.). Guerras por toda parte. Conflitos armados que impactaram a independência do Brasil. São Paulo: Alameda, 2023, 181 p.